The Establishment and Evaluation Method of Prefabricated Building Construction Quality Evaluation Index System Taking into Account Multimedia Sensor Network Nodes - Yankun Guo (Advances in Multimedia)
Through in-depth analysis of the characteristics of the quality evaluation stage of prefabricated buildings, the quality evaluation of prefabricated buildings can be divided into three stages: before, during, and after construction. According to the detailed design content of the prefabricated building construction stage, we construct the prefabricated construction quality evaluation index system, use the multimedia sensor network node method to obtain the weight of each evaluation index, comprehensively evaluate the construction quality of the prefabricated building, and finally show through the case analysis results that the multimedia sensor network node method can be of high practical value in the process of prefabricated building construction quality evaluation, and it has improved the domestic prefabricated building construction quality evaluation index system and evaluation quality and has certain reference value.